Ammonia removal from poultry manure leachate via struvite precipitation: a strategy for more efficient anaerobic digestion. (2017) - Farrow, Cameron; Crolla, Anna; Kinsley, Chris; McBean, Ed
To improve poultry waste management, the feasibility of enabling efficient anaerobic digestion of poultry manure through reduction of ammonia accumulation is examined. This study employs struvite precipitation to control ammonia accumulation, and focuses on the efficacy of ammonia removal under neutral reaction conditions (pH = 7). The impacts of phosphate and magnesium additives, pH, temperature and the N:Mg:P molar ratio are quantified. Magnesium chloride (MgCl2 • 6H2 O) and monopotassium phosphate (KH2 PO4 ) are shown to be the most efficient combination of additives for total ammoniacal nitrogen (TAN) reduction of poultry manure leachate under neutral reaction conditions (pH = 7), demonstrating a TAN reduction of 90.3%. Modification of molar ratios (NH4 :Mg:PO4 ) evidenced no significant benefit with regard to TAN reduction. However, increasing the fraction of supplementary magnesium resulted in a statistically significant (p < 0.05) decrease in phosphate concentration within the leachate. This study demonstrates the advantages of struvite precipitation, as a method of ammonia control, to improve anaerobic digestion and hence management of poultry manure. Although an effective means of TAN control, struvite precipitation from poultry manure is an ineffective means of obtaining pure struvite due to the formation of co-precipitates.